Factors affecting incident of stunting in children under five years - Siti Zullaiha; Yuliasti Eka Purnamaningrum; Mina Yumei Santi (Jurnal Kesehatan Ibu dan Anak, 2021)
Many children under five in Indonesia still suffer from stunting. Infant birth weight, exclusive breastfeeding, complementary feeding, and history of diarrheal disease/ARI are the factors that influence the incidence of stunting. The purpose of this study was to determine the factors that influence the occurrence of stunting in children in the work area of ??the Patuk I Public Health Center Gunungkidul. Research design using case control. The population was children aged 25-59 months using a sample of 78 cases, and 78 control groups, by purposive sampling method. Data were collected from the Patuk I Public Health Center report and interviews which were analyzed by chi-square and logistical regression. The proportion of stunting children was 23.9%. Chi-square analysis showed the baby's birth weight (p=0.010 OR=2,800), exclusive breastfeeding (p=0,000 OR=4,237), and complementary feeding (p=0,000 OR=5,223). While the history of diarrheal disease/ARI (p= 0.398 OR=1.572) was not a risk factor for stunting. The factor that most influenced the incidence of stunting was complementary feeding (p-value 0.000) with a risk of stunting 6.1 times. There are relationships between birth weight, exclusive breastfeeding, complementary feeding, and history of diarrheal disease/ARI with the incidence of stunting. Complementary feeding was the most influential factor in the stunting presence.